Skrining Hipertensi pada Pendonor Darah di Kabupaten Rembang - Adita Puspitasari Swastya Putri; Astri Dewi Ayu Kartika (Jaringan Laboratorium Medis, 2022)
Hypertension is one of the non-communicable diseases that is the cause of death in the world. WHO estimates the prevalence of hypertension is 22% of the total world population. Patients with hypertension often do not realize that they have hypertension and only find out after experiencing complications, so health screening is necessary. Blood donation in Rembang Regency also check their blood pressure before donating their blood. This can be a positive effort to improve health, control and manage signs and symptoms that arise. The purpose of this study was to screening blood donation for hypertension in Rembang Regency. This research is an observational study with a cross sectional design. The population in this study were voluntary blood donation who donated their blood during the month of Ramadhan at PMI Rembang Regency in 2018-2020 with a total sample of 260 blood donations. The sampling technique used in this research is simple random sampling. Based on data from blood donation in Rembang Regency, the results showed that most of the blood donation were male, as many as 221 (85.0%) blood donations and most of them aged 25-34 years, namely 81 (31.2%) blood donations. Most of the blood donation were included in the pre-hypertension category as many as 226 (86.0%) blood donations, and there were 12 (4.6%) blood donations included in the hypertension I category.